2021
DOI: 10.3390/molecules26206262
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Antitumor Unsymmetrical Bisacridines on 3D Cancer Spheroids Growth and Viability

Abstract: The culture of 3D spheroids is a promising tool in drug development and testing. Recently, we synthesized a new group of compounds, unsymmetrical bisacridines (UAs), which exhibit high cytotoxicity against various human cell lines and antitumor potency against several xenografts. Here, we describe the ability of four UAs—C-2028, C-2041, C-2045, and C-2053—to influence the growth of HCT116 and H460 spheres and the viability of HCT116 cells in 3D culture compared with that in 2D standard monolayer culture. Spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…In our Department, we have developed a new group of compounds, unsymmetrical bisacridines (UAs), which exhibited high cytotoxicity against numerous human cancer cells and antitumor activity against several xenografts [ 3 ]. Additionally, UAs turned out to be very potent in inhibiting the growth of HCT116- and H460-derived spheroids [ 27 ]. Moreover, some of the UAs were conjugated with quantum dots (QDs), which improved their delivery to cancer cells [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our Department, we have developed a new group of compounds, unsymmetrical bisacridines (UAs), which exhibited high cytotoxicity against numerous human cancer cells and antitumor activity against several xenografts [ 3 ]. Additionally, UAs turned out to be very potent in inhibiting the growth of HCT116- and H460-derived spheroids [ 27 ]. Moreover, some of the UAs were conjugated with quantum dots (QDs), which improved their delivery to cancer cells [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that C-2041 differed in its way of cellular action from other UAs and that cells treated with this derivative underwent more nonspecific cell death. Here, it is worth to mention that in studies concerning the influence of UAs on 3D spheroids cultures, C-2041 was the compound that inhibited the growth of both HCT116 and H460 spheroids to the least extent [ 27 ]. Another noteworthy observation is that C-2053 was the derivative, which was the least active against HCT116 colon cells, but one of the most potent ones against H460 lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the compounds which displayed the highest activity strongly inhibited pancreatic cancer cell lines [3]. Studies on the biological effects of these compounds demonstrated their ability to suppress 3D cancer spheroid growth [4]. Moreover, their anticancer activity was enhanced when bound to quaternary quantum dots, resulting in selective upregulation of their cellular uptake [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…UAs exhibited high cytotoxic activity against all 14 tested cancer cell lines as well as antitumor activity after screening in 10 human tumor xenografts in nude mice and against Walker 256 adenocarcinoma [3]. Studies on biological effects of these compounds demonstrated their ability to in uence 3D cancer spheroid growth [4]. Moreover, their anticancer activity was improved when bound to quaternary quantum dots, which selectively up-regulate cellular uptake of these compounds [5][6][7].…”
Section: Introductionmentioning
confidence: 99%